Surveillance cameras and their impact on stopping deviant behavior from the point of view of the Anbari community, Fallujah as a model - Abedalraazzaq jasseim mahmood /Ahmed mohammed mutlaq ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The aim of the research is to identify the role of surveillance cameras and their impact on curbing deviant behavior from the point of view of society, and came through the researchers’ focus on the changes that the world is witnessing, and the qualitative leap that shortened it a lot of time and effort in dealing with societal security requirements against behavioral deviations such as theft, addiction and sexual harassment And extremism that may appear as a result of social, economic and subjective factors that threaten its security, among these means are surveillance cameras, which have become the watchful eye in every time and place, whereby their presence has changed a lot of individuals’ behavior in terms of discipline and a sense of security, which is reflected on security in general, as it has proven a lot of Studies The effect of the camera on changing the behavior of individuals and changing the way they think. The researchers used the descriptive method. The study sample amounted to (283.625739) from the study population in the city of Fallujah for the year 2020/2021. One of the most important results of the research was that the camera contributes to easily identifying the thief: first for girls and fourth for males, while a section that controls the camera occupied the violations committed by some vehicle drivers on the external roads, the first for males and the second for females. A paragraph: The camera contributes to the speed of crime detection in the third place for both sexes, and a paragraph that helps the camera in detecting crime traces with high accuracy ranked fourth among females and fifth in males. A paragraph that helps the camera find out when the criminal will leave and return home is ranked fifth among both sexes. This agreement shows the spread of the phenomenon of using the camera in many homes, markets and companies, so that the person feels as if he is under constant surveillance, which prompted him to avoid many of the behaviors that may be recorded on him. DOI /10.54633/2333-021-042-004